Afterword: Does Deliberative Democracy Have a Role in Our Time of Political Crisis?. Issue 1 (26th August 2020) - Fung, Archon
Since the first generation of deliberative democratic theory, and the 'deliberative turn' in the 1990s, many societies around the world have become more institutionally fragile, multi-dimensionally unjust, and deeply divided. Does deliberative democracy have a constructive role to play in in these more challenging times in politics? As scholars of deliberation widen their ambit to explore broader forms of political communication, interactions between directly deliberative and non-deliberative institutions, and the roles for forms of highly adversarial political action, developments in deliberative democratic theory can help to guide efforts to strengthen our institutions in the short term and create political arrangements that are more just and democratic in the longer term.